Proneurotrophins Induce Apoptotic Neuronal Death After Controlled Cortical Impact Injury in Adult Mice. (June 2020) - Montroull, Laura E.; Rothbard, Deborah E.; Kanal, Hur D.; D'Mello, Veera; Dodson, Vincent; Troy, Carol M.; Zanin, Juan P.; Levison, Steven W.; Friedman, Wilma J.
The p75 neurotrophin receptor (p75NTR) can regulate multiple cellular functions including proliferation, survival, and apoptotic cell death. The p75NTR is widely expressed in the developing brain and is downregulated as the nervous system matures, with only a few neuronal subpopulations retaining expression into adulthood. However, p75NTR expression is induced following damage to the adult brain, including after traumatic brain injury, which is a leading cause of mortality and disability worldwide. A major consequence of traumatic brain injury is the progressive neuronal loss that continues secondary to the initial trauma, which ultimately contributes to cognitive decline. Understanding mechanisms governing this progressive neuronal death is key to developing targeted therapeutic strategies to provide neuroprotection and salvage cognitive function. In this study, we demonstrate that a cortical impact injury to the sensorimotor cortex elicits p75NTR expression in apoptotic neurons in the injury penumbra, confirming previous studies. To establish whether preventing p75NTR induction or blocking the ligands would reduce the extent of secondary neuronal cell death, we used a noninvasive intranasal strategy to deliver either siRNA to block the induction of p75NTR, or function-blocking antibodies to the ligands pro-nerve growth factor and pro-brain-derived neurotrophic factor. We demonstrate that either preventing the induction of p75NTR or blocking the proneurotrophin ligands provides neuroprotection and preserves sensorimotor function.